Meta-analysis: p16INK4α (Cyclin Dependent Kinase Inhibitor 2A) is one of the major causes of nasopharyngeal cancer - Lao Đức Thuận; Nguyễn Thị Ngọc Thảo; Thiều Hồng Huệ; Nguyễn Trung Hiếu; Phạm Thị Thúy Ngọc; Trần Bích Thư; Lê Huyền Ái Thúy (Tạp chí Khoa học Đại học Mở Thành phố Hồ Chí Minh - Kỹ thuật và Công nghệ)
Nasopharyngeal carcinoma (NPC) is a rare type of tumor originating from the region behind the nasal cavity and above the throat. The primary causes of NPC include Epstein-Barr virus infection, genetic mutations, and environmental factors, such as lifestyle. Global and Vietnamese studies have indicated enhanced methylation in the promoter region of CpG islands, contributing to the development of various cancers, including NPC (Chan, Teo, & Johnson, 2002). The p16INK4α gene, also known as cyclin-dependent kinase inhibitor, is a tumor suppressor gene that inhibits Cyclin-Dependent Kinase (CDK), leading to the inhibition of CDK interaction with cyclin, thereby inhibiting the phosphorylation process on pRb, halting the cell cycle. The p16INK4α gene is located on the short arm of chromosome 9 at position 9p21.3, consisting of three exons encoding 156 amino acids (Coppé et al., 2011). According to a meta-analysis of 11 papers on methylation processes on the p16 INK4α gene conducted by Xiao et al. in 2016, significantly higher levels of methylation were found in NPC tissue samples compared to non-tumor samples (Xiao et al., 2016). Additionally, methylation on the p16INK4α gene in blood samples from NPC patients was also significantly higher compared to normal blood samples. Therefore, this article aims to provide further scientific evidence on the enhanced methylation status in the promoter region of CpG islands of NPC patients based on the analysis of the p16INK4α gene using statistical synthesis methods. The research results demonstrated an uneven expression frequency of the p16INK4α gene between the two patient groups and the control group. In the patient group, we observed a Q value of 104.5223 with degrees of freedom (DF) = 13 and a p-value < 0.0001, along with an I2 index of 87.56%, with a 95% confidence interval for I2 from 80.84 to 91.9. Meanwhile, in the control group, the Q value was 56.1888 (p < 0.001), and the I2 index reached 76.86%, with a 95% confidence interval for I2 from 61.38 to 86.14. The weighted frequency of the patient and control groups was 63.478% and 7.966%, respectively, indicating a significant difference between the patient and control groups, with a high Q value and a very low p-value. Other factors that may influence the methylation process, such as ethnicity and sample source, were also included in the analysis. The results showed a significant correlation between the methylation process in these two groups and the development of NPC. Specifically, the Odds Ratios (OR) for China and Africa were 7.002 and 6.47, respectively. We also observed that the OR for samples from the mucosa and body fluids were 6.802 and 5.516, respectively. The analysis confirmed that the expression of the p16INK4α gene is strongly related to the formation of throat cancer. Therefore, this data provides a foundation for experimental studies on NPC samples collected from the Vietnamese population.